The molecular analysis of the shade avoidance syndrome in the grasses has begun - Kebrom, Tesfamichael H (Journal of experimental botany, 2007)
The shade avoidance syndrome (SAS) is a morphological and physiological response initiated by a decrease in light quantity and a change in light quality. Recent work in Arabidopsis thaliana has begun to define the molecular components of the SAS in a model dicot species, but little is known of these networks in agronomically important grasses. The focus of this review is to present a current view of the SAS in the grasses based largely on the characterization of mutants in the phytochrome signal transduction pathway and on the effects of far-red light treatments on plant growth. In cereal grasses, intense selection by plant breeders has acted to attenuate some but not all shade avoidance responses within modern crop varieties. Traditionally, breeding efforts have been focused on optimizing grain yield. However, with the recent interest in lignocellulosic-based biofuels, a new breeding paradigm may emerge to optimize biomass at the expense of grain yield. Some of the opportunities and challenges for engineering plant architecture to maximize resource use efficiency and yield by targeting the SAS in grasses are discussed